Relevanz und Potential von TikTok für die Social-Media-Marketing-Strategie von Unternehmen - Tanja Zweigle; Paul Hellinghausen (IU Internationale Hochschule, 2021)
– The video platform TikTok is one of the fast-growing social media apps. In Germany, nearly 15 million people are already using the platform, especially Generation Z. This is why TikTok is increasingly becoming the focus of many companies as a relevant social media platform. The aim of the study is to uncover the relevance and potential of TikTok as part of the social media marketing strategy for companies. The study is based on three qualitative interviews with social media experts from companies in the telecommunications, financial services and industrial sectors. All companies are already using TikTok and have relevant experience. To evaluate and analyse the content of the interviews, grounded theory was used to some extent. Main result of the analysis is that appealing to Gen Z, reached through authentic and native content, is a great potential of TikTok in the companies' social media strategy. In addition, an impact on brand image can be achieved through the use of the platform. The exponential organic reach also offers companies the opportunity to build high visibility and thus higher brand awareness. All three factors (targeting, brand image, reach) also lead to TikTok offering companies the opportunity to reach out to potential Gen Z applicants and attract them as employees. Based on the findings of the study, recommendations for action are made for companies on how they can use TikTok successfully. The challenges of this social media platform are also discussed.
urn:nbn:de:101:1-2021121709104855386703
Keywords: M30; 650; TikTok; Marketing; Social Media; Social Media Strategy